1992
DOI: 10.1007/bf02246258
|View full text |Cite
|
Sign up to set email alerts
|

Use of moclobemide in children with attention deficit hyperactivity disorder

Abstract: A monoamine oxidase hypothesis for the cause of attention deficit hyperactivity disorder has recently been established (Shekim et al. 1986). To test this, moclobemide, a new and reversible inhibitor of monoamine oxidase-A, was administered to 12 children between the ages of 6 and 13 years, diagnosed as attention deficit hyperactive according to DSM III-R, in a 4-week study. All had previously discontinued treatment with methylphenidate due to side-effects. A 40% improvement in parental assessment of children's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(13 citation statements)
references
References 9 publications
0
12
0
1
Order By: Relevance
“…Other potential therapeutic uses and indications can be smoking cessation, attention deficit, hyperactivity disorder and cognitive deficits in dementia for moclobemide [2][3][4].…”
Section: Therapeutic Use: Indications and Clinical Efficacymentioning
confidence: 99%
“…Other potential therapeutic uses and indications can be smoking cessation, attention deficit, hyperactivity disorder and cognitive deficits in dementia for moclobemide [2][3][4].…”
Section: Therapeutic Use: Indications and Clinical Efficacymentioning
confidence: 99%
“…Rommelse et al 2008) found a significant association of a more active MAOA allele with ADHD; this would depress vesicular stores and exocytotic release of dopamine and serotonin, but the concentration of synaptic transmitter would be restored by reuptake inhibitors such as MPH (Guimarães et al 2009). In several small studies, MAO inhibitors were shown to be as effective as amphetamine in reducing ADHD symptoms with comparable or fewer side effects (Mohammadi et al 2004;Rubinstein et al 2006;Trott et al 1992;Zametkin et al 1985). However, most of these studies used orally administered l-deprenyl (selegiline), which is an irreversible inhibitor of the type B form of MAO.…”
Section: Sex Cigarettes and Maomentioning
confidence: 99%
“…If overactive MAO plays a role in ADHD, inhibitors of MAO should ameliorate its symptoms, as they will slow the deamination of MAO (Bortolato et al 2008). Indeed, selegiline is just as effective as methylphenidate in treating the symptoms of ADHD (Akhondzadeh et al 2003;Mohammadi et al 2004), as is another MAO inhibitor, moclobemide (Trott et al 1992). Whereas the advantage of these drugs over more traditional pharmacotherapies is not established, new MAOIs (Youdim and Weinstock 2004) and routes of administration (Azzaro et al 2007) may lead to more effective pharmacotherapies.…”
Section: Materials Causes: Brain Modificationmentioning
confidence: 99%
“…Outside the psychostimulants, noradrenergic and dopaminergic active compounds including monoamine oxidase inhibitors [32,33], secondary amine tricyclic antidepressants [34] and bupropion [35] have been found superior to placebo in controlled clinical studies. Possible advantages of these compounds over stimulants include a longer duration of action without symptom rebound, minimal risk of abuse and as the potential treatment of comorbid internalizing symptoms.…”
Section: Second-line Agentsmentioning
confidence: 99%